1987
DOI: 10.1128/iai.55.1.162-168.1987
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and disulfide cross-linking of outer membrane components during the growth cycle of Chlamydia trachomatis

Abstract: The synthesis and accumulation of Chlamydia trachomatis outer membrane proteins within infected HeLa 229 host cells were monitored by assessing the uptake of [35S]cysteine into chlamydial proteins during the 48-h growth cycle of a lymphogranuloma venereum strain, L2/434/Bu. Synthesis of the major outer membrane protein, a protein that accounts for about 60% of the outer membrane protein mass of elementary bodies (EB), was first detected between 12 and 18 h after infection. The uptake of [35SJcysteine into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
1
2

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 20 publications
3
67
1
2
Order By: Relevance
“…Varied nutrient limitation and growth rate are known to lead to alteration in the synthesis of bacterial outer membrane proteins [19]. Thus, synthesis of the cysteine-rich proteins associated with RB-EB differentiation [20][21][22], whose expression is under strict gene regulation [23], may well have been impaired [1]; these proteins have been reported absent from penicillin-induced chlamydial forms [23,24]. A possible explanation for our findings may be that under amino acid limitation chlamydial multiplication is affected by interference with the expression of genes encoding the penicillin-binding proteins [25] -enzymes known to be involved in envelope expansion and septum formation in other bacteria, and suggested to be functionally active in Chlamydia [25].…”
Section: Discussionmentioning
confidence: 99%
“…Varied nutrient limitation and growth rate are known to lead to alteration in the synthesis of bacterial outer membrane proteins [19]. Thus, synthesis of the cysteine-rich proteins associated with RB-EB differentiation [20][21][22], whose expression is under strict gene regulation [23], may well have been impaired [1]; these proteins have been reported absent from penicillin-induced chlamydial forms [23,24]. A possible explanation for our findings may be that under amino acid limitation chlamydial multiplication is affected by interference with the expression of genes encoding the penicillin-binding proteins [25] -enzymes known to be involved in envelope expansion and septum formation in other bacteria, and suggested to be functionally active in Chlamydia [25].…”
Section: Discussionmentioning
confidence: 99%
“…The observations of Stirling et al [18] based on metabolic studies, supported the view that the formation of cysteine-containing structures is essential in RB-EB transformation, since conversion of RBs to EBs is severely retarded in the absence of cysteine in the growth medium. Further studies by Hatch et al [5] showed that EBs but not RBs harvested 21 h postinfection, contained extraordinarily cysteine-rich outer membrane proteins of 60 K and 62 K. The time and extent of synthesis of cysteine-rich proteins seems to be regulated by processes that coincide in time with transformation of RBs to EBs [7].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report, Newhall [7] showed that the 60 K and 62 K proteins of C. trachomatis LGV2 serotype were extensively cross-linked during most of the growth cycle. Newhall suggested that these data may indicate an intracellular, possibly enzymatic, cross-linking mechanism, present in addition to an auto-oxidation mechanism that occurs upon host cell lysis and exposure to extracellular environment [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EBs and RBs are morphologically and functionally distinct, EBs being 0.2 to 0.4 (xm in diameter W\th hyperpyknotic DNA and incapable of cell division, and RBs being ab?ut 1 M-m in diameter with dispersed DNA and incapable of host-oell infection (Costerton et ai, 1976). A few proteins found in EBs but not in dividing RBs have been identified (Hacl<stadt, 1986;Hatch et ai, 1984;Newhall, 1987;Wager and Stephens, 1988;Wenman and Meuser, 1986), and some developmental cyole stage-specific genes have been cloned and sequenced (Allen etai, 1990;Allen and Stephens, 1989;Clarke ef a/., 1988;Hackstadtefa/., 1991;Lambdenefa/., 1990;Perara etai, 1992;Tao etai, 1991). However, the mechanisms responsible for stage-specific gene expression have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%